Scoping Review: Hubungan Obesitas dengan Kejadian Osteoarthritis Lutut pada Lansia - Bunga Bella Alvionita; Ratna Dewi Indi Astuti; H. Iwan Tatang Hermawan (UNISBA Press, 2022)
Abstract. Osteoarthritis One of the most common joint problems in the elderly is knee pain. At this time, a person's life expectancy is quite high, but a life expectancy that is not balanced with health will reduce the quality of life. One of the risk factors for osteoarthritis most associated with obesity. Excess body weight will increase the burden on the knee joint. The purpose of this study was to analyze the relationship between obesity and the incidence of osteoarthritis knee in the elderly. This research is a scoping review. The databases used are PubMed, Springer Link, and Science Direct. Articles that meet the inclusion criteria from journals' full text, English, cohort or case control. There are 1,224 articles that meet the inclusion criteria are 1,224, and those that are included in the exclusion criteria are 1,219 articles. After a critical review, there were 5 articles that passed. The results of the analysis of article 5, stating that there is a relationship of obesity and osteoarthritis, show that knee with osteoarthritis have a higher BMI, and picture radiology Images reveal a more meaningful relationship in the obese, and obesity is associated with the severity of osteoarthritis of the knee. This was assessed by radiographic classification of osteoarthritis Ahlback. The conclusion of this study is that there is a relationship between obesity and the incidence of osteoarthritis knee in the elderly, while normal weight is not associated with osteoarthritis knee in the elderly. And obesity can worsen the radiographic results of osteoarthritis in the elderly. Abstrak. Osteoarthritis lutut merupakan salah satu masalah persendian pada lansia. Pada saat ini usia harapan hidup seseorang cukup tinggi, tetapi harapan hidup yang tidak diimbangi dengan kesehatan maka akan menurunkan kualitas hidup. Salah satu faktor risiko osteoarthritis lutut yang paling berkontribusi ialah obesitas. Berat badan yang berlebih, akan memperberat beban sendi lutut. Tujuan penelitian ini adalah untuk menganalisis hubungan antara obesitas dengan kejadian osteoarthritis lutut pada lansia. Penelitian ini merupakan Scoping Review. Database yang digunakan PubMed, Springer Link, dan Science Direct. Artikel yang sesuai dengan kriteria inklusi dari jurnal full text, berbahasa inggris, kohort atau case control. Artikel yang sesuai dengan kriteria inklusi sebanyak 1.224 artikel dan yang termasuk kriteria ekslusi sebanyak 1.219 artikel. Setelah dilakukan telaah kritis, artikel yang lolos sebanyak 5 artikel. Hasil analisis 5 artikel, menyatakan bahwa terdapat hubungan obesitas dan osteoarthritis lutut, penderita osteoarthritis lutut memiliki BMI lebih tinggi, gambaran radiologi osteoarthiritis lutut menampakan gambar yang lebih bermakna pada penderita obesitas, dan obesitas berhubungan denga n tingkat keparahan osteoarthritis lutut yang dinilai melalui klasifikasi radiografi osteoarthristis Ahlbäck. Kesimpulan dari penelitian ini adalah terdapat hubungan antara obesitas dan kejadian osteoarthritis lutut pada lansia, sedangkan berat badan normal tidak berhubungan dengan osteoarthritis lutut pada lansia. Serta obesitas dapat memperburuk hasil radiografi dari osteoarthritis lutut pada lansia.